2021
DOI: 10.1111/nph.17636
|View full text |Cite
|
Sign up to set email alerts
|

Severance of arbuscular mycorrhizal fungal mycelial networks in restoration grasslands enhances seedling biomass

Abstract: Establishment and growth of grassland plant species is generally promoted by arbuscular mycorrhizal fungi (AMF) when grown in isolation. However, in grassland communities AMF form networks that may connect individual plants of different ages within and between species. Here, we use an ingrowth core approach to examine how mycorrhizal networks influences performance of seedlings in grasslands.We selected four grass and four forb species with known negative or neutral-positive plant-soil feedback and grew them i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Possible explanations of the less negative PSF in juveniles is that they are less affected by nutrient depletion, are less sensitive to specialized soil pathogens, or benefit more from associations with arbuscular mycorrhizal fungi due to a less developed root system (van der Heijden 2004, Aldrich‐Wolfe 2007). On the other hand, there is also evidence of negative effects of AMF colonization on seedlings growth (Dassen et al 2021). Seed germination may be also positively affected by plant growth‐promoting rhizobacteria (Kloepper et al 1991, Wu et al 2016) which may be stimulated by root exudates released by some plants (van Loon 2007, Vacheron et al 2013, Hu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations of the less negative PSF in juveniles is that they are less affected by nutrient depletion, are less sensitive to specialized soil pathogens, or benefit more from associations with arbuscular mycorrhizal fungi due to a less developed root system (van der Heijden 2004, Aldrich‐Wolfe 2007). On the other hand, there is also evidence of negative effects of AMF colonization on seedlings growth (Dassen et al 2021). Seed germination may be also positively affected by plant growth‐promoting rhizobacteria (Kloepper et al 1991, Wu et al 2016) which may be stimulated by root exudates released by some plants (van Loon 2007, Vacheron et al 2013, Hu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These, in exchange for a number of products assimilated by photosynthesis [14], protects against pathogens [15][16][17], limits abiotic stresses [18][19][20][21][22] and restricts the heavy metals of the host species [23][24][25]. In addition, mycorrhizal fungi interconnect with the grassland species through a network of hyphae [26], thus intervening in the dynamics of the plant community [27,28]. It has been shown that the involvement of plants in a symbiotic partnership with mycorrhizal fungi can lead to the dominance of some species, as well as to the exclusion of other plants [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Although the influence of the richness of the mycorrhizal community could not been detected statistically, the mutualistic interaction will have contributed to the relative effect of the competition between the plants . AMF mutualists can promote plant species coexistence Hart et al, 2003) but have also been shown to generate negative effects on the biomass of establishing seedlings (Dassen et al, 2021). The relative strength of these effects is governed by an interplay of several factors like the identity of the early and late arriving plants , and their AMF community composition and richness , which makes it difficult to separate these factors in my results.…”
Section: Competition For Resources Not Interaction Niche Properties D...mentioning
confidence: 93%